Relationship between Nutrition Knowledge, Breakfast Habits, Snack Practices with Students' Nutrition Status - Rahayu, Dewi; Aulia, Vivi; Arsil, Yuliana; Aziz, Alkausyari (JURNAL PROTEKSI KESEHATAN, 2024)
Good nutritional status is obtained from fulfilling the need adequate food intake. Children's nutritional needs can be met with 3 main meals a day and healthy snacks. But the fact is that there are still many children who leave the breakfast habit. School children cannot be separated from snacks. One of the factors that influence the selection of snacks and breakfast is nutritional knowledge. Children who have good breakfast and snack habits can fulfill their nutritional needs so that there is no deficiency or excess of nutritional status. The purpose of this study was to determine the description of nutritional knowledge, breakfast practices and snacks for students at SDN 11 Bathin Solapan, Bathin Solapan District. The sample of this research were grade IV and V students totalling 55 people with proportional random sampling. This study uses primary data by interview method. The results obtained were 69.1% of respondents nutritional knowledge in the moderate category, 36.4% never had breakfast in a week, 80% of respondents snacked 3 times a day, and 70.9% of respondents had good nutritional status.